Perancangan Aplikasi Taman Alat BMKG Wilayah 1 Medan Berbasis Android - Samsudin, Samsudin; Husna, Fauziatun; Wulandari, Novika; Ginting, Natal (Jurnal Ilmiah Sains dan Teknologi, 2024)
The Meteorological Equipment Park is a park in which there are several tools for observing meteorological parameters. The Tool Garden contains several tools for observing surrounding weather elements. This application aims to increase efficiency in monitoring and management of meteorological and geophysical tools. With a focus on the user interface, this application is designed to provide information regarding what tools are available at the Meteorology, Climatology and Geophysics Agency (BMKG) Region 1 Medan. The result of this research is the creation of an Android-based BMKG Region 1 Medan Tool Park Application for the community and BBMKG Region 1 Medan using the stages in the (RAD) method, namely Requirements Planning, Design Workshop, and Implementation.